Pengaruh Penggunaan Media Visual Wayang Terhadap Kemampuan Bahasa Ekspresif Pada Anak Usia 5-6 Tahun Di TK Karya Perumnas - Nurfadilla Nurfadilla; A. Sri Wahyuni Asti; Hasmawaty Hasmawaty (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2026)
This study aims to determine the effect of visual media use on expressive language in 5-6 year old children at Karya Perumnas Kindergarten. The research approach used is a quantitative approach with a quasi-experimental design. The population in this study were children in group B aged 5-6 years at Karya Perumnas Kindergarten. The research population consisted of 10 children in group B1 and 10 children in group B2. Purposive sampling was used to collect samples. The sample in this study consisted of 20 children aged 5-6 years in group B, with 10 children in the experimental group and 10 children in the control group. The data collection techniques used in this study were observation, testing, and documentation. The data analysis technique used was descriptive statistical analysis and non-parametric analysis using the Wilcoxon Sign Rank Test version 23. Based on the results of the study, it can be concluded that the expressive language skills of children who were given treatment using visual puppet-based media in the experimental group were better than those in the control group. The results of the data analysis showed an average increase of 25.00 in the experimental group and 19.00 in the control group. The test results showed that sig. (2-tailed) 0.003 < 0.05, so H0 was rejected and H1 was accepted. Therefore, it can be concluded that visual -based learning media has an effect on the expressive language skills of 5-6 year old children at Karya Perumnas